Pengaruh Slow Deep Breathing terhadap Penurunan Tekanan Darah pada Pasien Hipertensi: Sebuah Tinjauan Sistematis - Yofa Anggriani Utama (Universitas Batanghari Jambi, 2023)
Hypertension is a non communicable diseases which is one of the main causes of death in the world. Hypertension is the third killer diseases, one of the diseases that can cause death in the world. . Hypertension requires treatment for a long time, if not given treatment, it can cause various complications. Non- pharmacological treatment efforts are usually done to lower blood pressure. One of the Non- pharmacological treatment that is not widely known is by using slow deep breathing therapy or slow deep breathing relaxation. The purpose of this study was to determine the effect of slow deep breathing on reduing blood pressure in hypertension patients. The research design used a systematic review using quantitative research methods. Based on the results of a systematic review, it was found that there is an effect of slow deep breathing on decline blood pressure in hypertension patients.